Perception of the Male Representatives Regarding the Role of Women Representatives in Urban Governance: A Case Study of Haryana State - Kamana (European Journal of Applied Sciences, 2023)
In urban governance male and women representatives both play important role in the development of the Municipalites. In urban governance representatives and executives both play important role in the development. The proper functioning of all urban local bodies is depending upon the coordination between the elected representatives. In urban governance these are represent the two strong pillers of the urban government. For the success of the urban governance good coordination and relationship between male and women representatives are required. With the reservation in municipalities women get a chance to take participation in the urban politics. At present there are many states who give 50 percent reservation to women in politics i.e., Himachal Pradesh, Karnataka, Kerela, Odissa, Tamil Naidu, MAharastra, Uttar Pradesh and now even Haryana state also give them. The main purpose of the study is to check the perception of the male representatives regarding the awareness and effective participation of women representatives in the growth and development of the urban local bodies. For the present study 60 male representatives were selected from the three different Municipalities of Haryana State i.e Sonipat, Panchkula and Jind Municipalities.